Growth and demise of Permian biogenic chert along northwest Pangea: evidence for end-Permian collapse of thermohaline circulation - Beauchamp, Benoît; Baud, Aymon (Palaeogeography, Palaeoclimatology, Palaeoecology, 2002)
The Permian Chert Event (PCE) was a 30 Ma long episode of unusual chert accumulation along the northwest margin of Pangea, and possibly worldwide. The onset of the PCE occurred at about the Sakmarian-Artinskian boundary in the Sverdrup Basin, Canadian Arctic, where it coincides with a maximum flooding event, the ending of high-frequency/high-amplitude shelf cyclicity, the onset of massive biogenic chert deposition in deep-water distal areas, and a long-term shift from warm- to cool-water carbonate sedimentation in shallow-water proximal areas. A similar and coeval shift is observed from the Barents Sea to the northwestern USA. A landward and southward expansion of silica factories occurred during the Middle and Late Permian at which time warm-water carbonate producers disappeared completely from the northwest margin of Pangea. Biotically impoverished and increasingly narrow cold-water carbonate factories (characterised by non-cemented bioclasts of sponges, bryozoans, echinoderms and brachiopods) were then progressively replaced by silica factories. By Late Permian time, little carbonate sediments accumulated in the Barents Sea and in the Sverdrup Basin. where the deep- to shallow-water sedimentary spectrum was occupied by siliceous sponge spicules. By that time, biogenic silica sedimentation was common throughout the world. Silica factories collapsed in the Late Permian, abruptly bringing the PCE to an end. In northwest Pangea, the end- Permian collapse of the PCE was associated with a major transgression and with a return to much warmer oceanic and continental climatic conditions. Chert deposition resumed in the distal oceanic areas during the early Middle Triassic (Anisian) after a 8-10 Ma interruption (Early Triassic Chert Gap). The conditions necessary for the onset, expansion and zenith of the PCE were provided by the thermohaline circulation of nutrient-rich cold waters along the northwestern and western margin of Pangea, and possibly throughout the world oceans. These conditions provided an efficient ...